Pengaruh Variasi Latihan Zi-Zag Run terhadap Kemampuan Dribbling pada Siswa Ekstrakurikuler Futsal di SMK Negeri 3 Pontianak - Angga Bagus Saputra; Wiwik Yunitaningrum; Doni Pranata; Mimi Haetami; Rizki Hazazi Ali (Journal on Education, 2025)
This study aims to determine the effect of Zig-Zag Run training variations on dribbling ability in futsal extracurricular students at SMK Negeri 3 Pontianak. The research method used is an experiment in the form of pre-experimental design. The source of data for this research is students of class X and class XI who participate in futsal extracurricular activities at SMK Negeri 3 Pontianak. The data are assessment sheets of dribbling ability before and after the implementation of variations of Zig-Zag Run exercises and the results of interviews with futsal extracurricular coaches. The results of the study showed that the provision of variations of Zig-Zag Run exercises had a significant effect on the dribbling ability with the ball in futsal extracurricular students at SMK Negeri 3 Pontianak. The dribbling ability of futsal extracurricular students at SMK Negeri 3 Pontianak before being given a variation of Zig-Zag Run practice obtained an average pretest score of 27,218. The dribbling ability of futsal extracurricular students at SMK Negeri 3 Pontianak after being given a variety of Zig-Zag Run exercises has increased with an average posttest score of 29.3045. There was a significant influence of the variation of the Zig-Zag Run practice on the dribbling ability of futsal extracurricular students at SMK Negeri 3 Pontianak, with a t-test result value of 8.095 on dribbling ability with the ball.